Comparison of diagnostic methods for uterine health in dairy cattle on different days postpartum. (25th January 2020) - Kusaka, Hiromi; Hasegawa, Ryo; Nishimoto, Namiko; Kawahata, Masatoshi; Miura, Hiroshi; Kikuchi, Motohiro; Sakaguchi, Minoru
Abstract : Background: Uterine health status is a key factor for dairy management. Methods: The uteri of 28 Holstein cows were assessed weekly by three different methods: ultrasonography (UT), Metricheck device (MT) and cytobrush (CYT), during two weeks to seven weeks postpartum. Results: The percentage of cows with an MT‐positive, UT‐positive and CYT‐positive result decreased dramatically at three weeks, four weeks and five weeks postpartum, respectively. The agreement of the results was poor or weak within six weeks postpartum (κ=0.09–0.35), and only at seven weeks moderate or good agreement was achieved (κ=0.60–0.70). When comparing the results obtained by UT and MT, 30 per cent or more of the total cows had conflicting results from postpartum three weeks to six weeks. The uterine health of cows was re‐evaluated by the combined usage of UT and MT referring to CYT. The highest sensitivity was achieved when positive individuals were identified as either MT‐positive or UT‐positive, whereas the highest specificity occurred when results were positive by both MT‐ and UT‐ methods. Conclusion: The accuracy of early postpartum uterine health status by three methods depended heavily on the time postpartum. The combined use of UT and MT is a practical candidate for cow‐side monitoring method of uterine health.